Impact of premorbid hypertension on haemorrhage severity and aneurysm rebleeding risk after subarachnoid haemorrhage. Issue 1 (29th June 2013) - De Marchis, Gian Marco; Lantigua, Hector; Schmidt, J Michael; Lord, Aaron S; Velander, Alan J; Fernandez, Andres; Falo, M Cristina; Agarwal, Sachin; Connolly, E Sander; Claassen, Jan; Mayer, Stephan A
Abstract : Objective: Arterial hypertension (HTN) is a risk factor for subarachnoid haemorrhage (SAH). We aimed to assess the impact of premorbid HTN on the severity of initial bleeding and the risk of aneurysm rebleeding after SAH. Design: Retrospective analysis of a prospective cohort study of all SAH patients admitted to Columbia University Medical Center between 1996 and 2012. Results: We enrolled 1312 consecutive patients with SAH; 643 (49%) had premorbid HTN. Patients with premorbid HTN presented more frequently as Hunt–Hess Grade IV or V (36% vs 25%, p<0.001) and World Federation of Neurosurgical Societies (WFNS) Grade 4 or 5 (42.6% vs 28.2%, p<0.001), with larger amounts of subarachnoid (Hijdra Sum Score 17 vs 14, p<0.001) and intraventricular blood (median IVH sum score 2 vs 1, p<0.001), and more often with intracerebral haemorrhage (20% vs 13%, p=0.002). In multivariate analysis, patients with premorbid HTN had a higher risk of in-hospital aneurysm rebleeding (11.8% vs 5.5%, adjusted OR 1.67, 95% CI 1.02 to 2.74, p=0.04) after adjusting for age, admission, Hunt–Hess grade, size and site of the ruptured aneurysm. Conclusions: Premorbid HTN is associated with increased severity of the initial bleeding event and represents a significant risk factor for aneurysm rebleeding. Given that aneurysm rebleeding is a potentially fatal—but preventable—complication, these findings are of clinical relevance.